PAMER KEKAYAAN DAN NORMALISASI KONSUMERISME DI MEDIA SOSIAL TIKTOK PERSPEKTIF ANALISIS WACANA KRITIS JAMES PAUL GEE - Muhammad Adnan Arsak; Sakaria; Muh, Bahly Basri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The rapid development of social media has transformed TikTok into a digital space that functions not only as a platform for entertainment but also as an arena for the construction of social meanings and consumer culture. This study aims to examine the representation of wealth-display practices and to uncover the process of consumerism normalization in TikTok content through the perspective of James Paul Gee’s Critical Discourse Analysis. The research employs a descriptive qualitative approach, using TikTok videos portraying luxurious lifestyles as the primary data source. The data, consisting of language, visual symbols, and digital narratives, were collected through observation, documentation, and note-taking techniques and were analyzed using the Miles and Huberman interactive model, which includes data reduction, data display, and conclusion drawing. The findings reveal that representations of wealth display are constructed through a combination of language, visuals, and narratives that emphasize material ownership as an indicator of success. Analysis based on the Seven Building Tasks of Language framework identifies seven dimensions of discourse construction: significance, practices, identities, relationships, politics, connections, and sign systems and knowledge. These dimensions contribute to shaping the perception that the consumption of luxury goods serves as a symbol of prestige, a means of constructing social identity, and a representation of an ideal lifestyle. The findings indicate that TikTok functions as a medium that reproduces and legitimizes consumerist values within contemporary digital culture.